2020
DOI: 10.3233/jad-190729
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Exercise Decreases Amyloid Load and Modulates Inflammatory Responses in the APP/PS1 Mouse Model for Alzheimer’s Disease

Abstract: Neuroinflammation has been shown to play a crucial role in the development of Alzheimer's disease (AD) and also has an association with amyloid-␤ (A␤) plaques, a hallmark of this disease. Physical exercise has emerged as an alternative treatment for pathological impairment in AD. In light of this evidence, together with the fact that the hippocampus is one of the first structures to be affected in AD, we analyzed hippocampal changes in A␤ load, inflammatory responses, and locomotor activity in transgenic APP/P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Our study demonstrated that long-term voluntary physical exercise significantly reduces IL-6 levels in plasma and the cortex of WT and 5xFAD exercised mice, while IL-6 levels in muscle remain unchanged. Consistent with our findings, previous studies have shown that IL-6 is attenuated in the brain after treadmill exercise of healthy rats [22] and after resistance exercise in APP/PS1 mice [23]. Moreover, a recent human study demonstrated that aging induces increases in serum IL-6, while lifelong aerobic exercise during 50 years decreases serum IL-6 with no differences observed in skeletal muscle IL-6 levels [78].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study demonstrated that long-term voluntary physical exercise significantly reduces IL-6 levels in plasma and the cortex of WT and 5xFAD exercised mice, while IL-6 levels in muscle remain unchanged. Consistent with our findings, previous studies have shown that IL-6 is attenuated in the brain after treadmill exercise of healthy rats [22] and after resistance exercise in APP/PS1 mice [23]. Moreover, a recent human study demonstrated that aging induces increases in serum IL-6, while lifelong aerobic exercise during 50 years decreases serum IL-6 with no differences observed in skeletal muscle IL-6 levels [78].…”
Section: Discussionsupporting
confidence: 92%
“…IL-6, a multifunctional cytokine that is paramount in immune responses and nervous system function, is increased in the brain during aging and AD [21]. In contrast, brain IL-6 levels are reduced upon regular physical exercise [22,23]. Exercise-induced IL-6 modulation remains poorly investigated in the context of AD.…”
Section: Introductionmentioning
confidence: 99%
“…Although research has focused on the effects of aerobic exercise (forced or voluntary exercise) in AD models (Nichol et al, 2007(Nichol et al, , 2008Xiong et al, 2015), less is known about the impact of resistance exercise on this pathology. Our group and others have recently shown that resistance exercise may minimize the alteration in exploratory activity (Hashiguchi et al, 2020) and in cognitive function (Liu et al, 2020) in a transgenic mouse model for AD.…”
Section: Physical Exercise In Adulthood Aging and Neurological Disordersmentioning
confidence: 97%
“…However, the unbiased estimation of the number of cells of interest by the stereological method is accurate [ 82 ]. Using the unbiased stereological method, Hashiguchi et al reported that 4 weeks of ladder-climbing exercise did not affect the total number of microglia in the dorsal hippocampus of APP/PS1 mice at the age of 8 months [ 83 ]; however, they did not quantify the number of microglia in the subregions of the hippocampus. In our study, we showed that long-term voluntary running significantly increased the total number of microglia in the DG of 13-month-old APP/PS1 mice.…”
Section: Discussionmentioning
confidence: 99%